Physicochemical Properties of Cassava Starch Retrograded in Alcohol - Mohammed Achor, James Yinka Oyeniyi, Mukhtar Musa, Mahmud Sani Gwarzo (Journal of Applied Pharmaceutical Science, 2015)
Starch is an important excipient employed in the pharmaceutical industry but irrespective of its source, the native starch is undesirable for many applications because of its inability to withstand processing conditions and hence the need for it modification in order to improve its desired properties. The objective of this study was to extract, modify by retrogradation in alcohol and evaluate starch obtained from Manihot esculentum as a pharmaceutical excipient. The starch was extracted then modified by retrogradation using alcohol for a period of 0, 24, 48 and 96 hrs. The granular morphology, amylose and amylopectin fractions, ash value, true density, powder porosity, swelling capacity, hydration capacity, moisture sorption capacity, bulk density, tapped density, Carr’s index, Hausner’s ratio, angle of repose, X-ray diffractography, elemental and proximate analysis were used for the physicochemical characterizations and was subsequently compared with native Manihot esculentum starch. Starch obtained by retrogradation showed decrease in angle of repose, moisture sorption capacity, moisture content, water solubility index and showed increase swelling capacity, hydration capacity and crystallinity as compared to the native starch. In conclusion, retrograded starch showed better pharmaceutical potentials than the native starch as evident to its improved physicochemical properties.
Keywords: Cassava starch, retrogradation, alcohol.